SISTEM INFORMASI PENDATAAN SURAT MASUK DAN SURAT KELUAR - Rita Hamdani (STMIK Pelita NUsantara, 2019)
Letters are one of the means of written communication used to convey information. The contents of the lettermust be accountable, because as documentation and as evidence if at any time needed. In STMIK PelitaNusantara Data collection of incoming and outgoing letters has weaknesses such as, the data is entered into aledger, with the large amount of data if using a ledger, it can make the data collection of incoming andoutgoing letters experience difficulties. Difficulties can be in the form of the difficulty of finding the dataneeded, the difficulty of making daily or monthly reports. So it is difficult to know whether there are incomingand outgoing letters. To facilitate the data collection of incoming and outgoing letters, it is necessary to use anapplication based on a database. This research was made using Visual Basic. Net 2010 application and thedatabase used was SQL Server 2008.